O impacto do aumento de despesas sobre a efetividade de atuação do judiciário cearense - Araújo, Antonia Tatiana Ribeiro (2016)
The objective of the present work is to demonstrate the impact of the increase from the main investments outflow and spending of the 1st instance of the State judiciary magistrate’s productivity, analyzing the evolution and effectiveness of the judiciary between 2007 and 2013. It was realize an econometric analyses about the increase impact of the outflow in the jurisdictional effectiveness, been analyze the Ceará´s State judiciary productivity and the budget of the main spending of people and investments. With the purpose of verifying if there is any link between the effectiveness of the judiciary’s work and the increase in their spending. The analyze was conducted with a base in the statistics from the CNJ (Conselho Nacional de Justiça – National Cônsul of Justice), more specificin the link “Justiça em Números e Justiça Aberta” of the Tribunal de Justiça´s internet page, at the links “Transparência TJCE e Meta 7 – Produtividade dos Magistrados”, and in the page “Secretaria do Planejamento e Gestão do Estado do Ceará” at the link “execução orçamentária”. This study has the purpose to contribute to an improvement of the institutional that is the judiciary, demonstrating the impact of the Ceará´s judiciary’s Power, taking in consideration the execution of the main investments outflow and spending. The practice of using econometric models allow us to verify, in spite of the small value of the judiciary productivity rate, it was increasing during the time analyzed. Based on the studied items, human capital was the only item that reach a significant statistical value, with a 5% percentage. The more you spend in human capital the result is a lower productivity and the investments applied in areas such as technology and training does not create relevant statistical variables.